Recent Advances in Metal/Alloy Nano Coatings for Carbon Nanotubes Based on Electroless Plating - Zhang, Lei; Chao, Yi; Yang, Kenan; Xue, Daodao; Zhou, Shisheng (Frontiers in Chemistry, 2022)
A large number of researches on the electroless plating of carbon nanotubes and their applications after plating have emerged, which has attracted more and more attention. In this review article, the existing electroless plating methods for carbon nanotubes were briefly summarized, and the surface coatings were listed and analyzed in detail. At last, the related applications after electroless metal/alloy coatings of carbon nanotubes were discussed in detail. This study aims to provide a reference for the research and improvement of different electroless metals/alloys coatings of carbon nanotubes. After a clear understanding of the electroless metal/alloy coatings of carbon nanotubes, the appropriate coating can be selected according to the actual situation, so that the carbon nanotubes after plating can be used as reinforcement and modification materials for better satisfaction of the needs, and the application of plated carbon nanotubes has reference significance in more fields.